Health Awareness Education Through Blood Checking in Pharmacies - Hermawatiningsih, Oktaviarika Dewi; Raising, Rahmawati; Basy, Lukman La; Maritha, Vevi (Jurnal IPMAS, 2024)
Increasing public health awareness is one of the main challenges in the health sector in Indonesia. Pharmacies not only play a role as a place to get medicine, but also as a means of health services that can provide education and basic health checks for the community. This education aims to increase public awareness about the importance of health and teach ways to maintain and improve the quality of life. Pharmacies that adopt blood testing services as part of health education programs can help reduce the burden on larger health services, such as hospitals and clinics. The educational activity to the community carried out at Apotek X Madiun City which lasted for 2 hours received a good response from the surrounding community. Where there were 35 participants who took part in blood tests and also gave various types of questions related to health. So that the provision of education and information to increase health awareness can be carried out properly. Health awareness education through blood checks in pharmacies is a strategic step in improving the quality of public health. With the strategic role of pharmacies, blood testing services can be an entrance for people to be more concerned about their health conditions.